Social representations of students regarding management and curriculum in two Costa Rican Technical Professional Colleges - Melendez Montero, Arturo (2025)
This article arises from broader research within the framework of the project Perfiles, Dinámicas y Desafíos de la Educación Costarricense belonging to the CIDE Universidad Nacional. In this project, the social representations (SR) of the students about two technical-professional institutions in Costa Rica were analyzed. To do this, the focus group strategy was applied and information was collected both in writing and graphically through the drawing technique. The results show that the SR built on both institutions are associated with the image of a hierarchical organization that centralizes the power to make decisions in the directors, excluding the students from the decision-making processes within the institution. In addition, an image linked to a high academic load, fatigue and stress is expressed, characteristics that are also associated with work life. The latter is thought by the students as the purpose of the educational process. It concludes with the need to give voice and participation to the students within educational institutions, considering them active subjects in the implementation of educational and curricular policies.